The improvement of Social Learning Quality By Using Sociodrama Method at State-Owned Junior High School41 Semarang - Munadjad, Imam (2012)
The objectives of this action class study are (1) To know the improvement of the quality of History learning process on the material of the born of the reform era with Sociodrama method at the ninth grade students of State-Owned Junior High School 41 Semarang. (2) to know the improvement of the quality of the History learning output on the material about the born of the reform era with the Sociodrama method at the ninth grade students of State-Owned Junior High School 41 Semarang. It is an action class research using two cycles. Those cycles consist of four activities such as planning the action, implementation of the action, observation, and reflection of the action. Data source includes event, teacher and student, curriculum, data of the number of student, result of evaluation. The success of this research can be seen from the result of written test. Data which are analyzed are in non test (during the learning process) and test (after the learning process). Data validity uses triangulation. The result of this research shows that (1) The use of learning model of Sociodrama can improve the quality of History learning process on the material of the birth of reformation era for the nine grade students of State-Owned Junior High School 41 Semarang. It is seen from the improvement of activity on the component of learning process that student's liveliness of 35.14% in cycle 1, becomes 48.65% in cycle 2. Student's discipline of 37.84% in cycle 1 becomes 51.35% in cycle 2. Student's motivation of 32.43% in cycle 1 becomes 56.76% in cycle 2. (2) The use of Sociodrama learning model can improve the quality of History learning output on the material of reform era for the nine grade student of State-Owned Junior High School 41 Semarang. In this case, the learning output is the result of student's test and student's learning completeness score. The average of student's learning output for cycle 1 is 69, for cycle 2 becomes 72. While the learning completeness score from 75.68% becomes 86.49%.